Autocorrelation Spatial Infrastruktur Transportasi di Jawa Tengah - Abdul Karim; Muhammad Saifudin Nur; Akhmad Faturohman (Universitas Muhammadiyah Semarang, 2017)
This paper describes the spatial dependence of road transport infrastructure in Central Java using Moran's global approach. The results show that road transport infrastructure in Central Java has a spatial dependence on alpha five percent. In addition, the value of Moran's index is positive which indicates that each adjacent area has a positive spatial dependence.Keywords: spatial autocorrelation, Moran's I, Spatial Dependency, Transportation Infrastructure.